The Effect of Electronic Payments on Customer Satisfaction (Case Study of the Al-Watani Islamic Bank Iraq) - Alfatlawi, Hayder Ali Kadhim; Alsaedi, Wasan Khifah Abdulridha (AL- IKTISAB Journal of Islamic Economic Law, 2023)
The research aims to identify the dimensions of electronic payments and the security requirements of the electronic payment system and indicate their impact on customer satisfaction. Because the banking sector in Iraq suffers from a changing banking environment, which requires it to keep abreast of developments in the system, and accordingly, the electronic payment service will have a future system for all forms of payments in all institutions. The researchers used the method analytical descriptive (quantitative) to explore the relationship and impact of electronic payments on customer satisfaction for employees in the Al-Watani Islamic Bank Iraq, where the necessary components were selected for each group using a random sample that included an official and an employee in the administration and its related branches for May and June 2023. The data collection tools were (questionnaire), where an electronic form (questionnaire) was distributed to (70) of the workers in this reserach. The responses averaged (61) responses, and a program was SPSS V.23 for statistical analysis and several methods and tools, descriptive analysis (central tendency measurement tools, statistical dispersion), simple linear regression, and quantitative analysis (pearson correlation coefficient). The researchers concluded that there is a direct correlation and a statistically significant effect between electronic payments and customer satisfaction under research at a significant level 0.01. The researchers recommend improving customer satisfaction by investing in modern protection technology, should make the process of registration and use of electronic banking services easy and simple, provide rewards and incentives to customers who use electronic payment, to carry out promotional campaigns to raise awareness of the benefits and safety of electronic payment, and how to use it effectively.